Iron curtains : gates, suburbs, and privatization of space in the post-socialist city - Hirt, Sonia (Hoboken, N.J. : Wiley & Sons, 2012)
Utilizing research conducted primarily with residents of Sofia, Bulgaria, Iron Curtains: Gates, Suburbs, and Privatization of Space in the Post-socialist City explores the human dimension of new city-building that has emerged in East Europe. Features original data, illustrations, and theory on the process of privatization of resources in societies undergoing fundamental socio-economic transformations, such as those in Eastern EuropeRepresents the sole in-depth monograph on contemporary urbanism in Southeast EuropeMakes a broader statement on issues of urbanism in Europe and other parts of the w.
Introduction -- Public, private, privatism -- The post-socialist city -- Post-modern urbanism revisited -- Sofia : wither the socialist city -- The ninth ring: suburbanizing Sofia -- Iron curtains I: gated homes -- Iron curtains II: gated complexes -- Architecture of disunity -- Possibilities -- Figures and tables -- Appendix -- References -- Notes.
Includes bibliographical references and index.
Print version record.
Keywords: 2000-2099; City planning -- Former communist countries; City planning -- Europe, Eastern; Property -- Former communist countries; Property -- Europe, Eastern; Gated communities -- Former communist countries; Gated communities -- Europe, Eastern; Equality -- Europe, Eastern; POLITICAL SCIENCE -- Public Policy -- Regional Planning; City planning; Equality; Gated communities; Property; Social conditions; Europe, Eastern -- Social conditions -- 21st century; Europe, Eastern; Former communist countries; Electronic books